Impact of Liquidity in Capital Market on Economic Growth in Nepal: A Toda-Yamamoto Approach - Phaju, Rajan (Khwopa Journal, 2025)
This study explores the dynamic relationship between liquidity in capital market, investor confidence, the NEPSE index, and economic growth (GDP) in Nepal using the Toda-Yamamoto Granger non-causality approach. The analysis is based on annual time-series data from 1994 to 2023. The key variables include log-transformed Gross Domestic Product (lnGDP), NEPSE index (lnNEPSE), liquidity in the capital market measured by the ratio of turnover to market capitalization (LCM), investor confidence proxied by the ratio of market capitalization to paid-up capital (IC), and a dummy variable (DUM) to capture the structural break identified in 2010. The findings reveal a unidirectional causal flow from investor confidence and market liquidity to the NEPSE index, indicating that sentiment and transactional efficiency significantly shape market performance. In turn, NEPSE exhibits a positive and significant impact on GDP, affirming the capital market’s role as a leading indicator of economic growth. The study identifies the presence of a structural regime shift in 2010, necessitating the inclusion of a dummy variable to capture changes in market dynamics postreform or due to macroeconomic changes. The results further suggest that capital market development indirectly influences economic growth through NEPSE, rather than through direct effects of liquidity or investor sentiment on GDP. The causal chain—from investor confidence and liquidity to NEPSE, and from NEPSE to GDP—underscores the capital market’s role as a transmission mechanism in the economy. Policy recommendations include enhancing investor protection, ensuring market transparency, encouraging real-sector listings, and aligning macroeconomic policies with capital market reforms. The study urges institutions like SEBON, NRB, and the Ministry of Finance to work in coordination to strengthen capital market infrastructure and policy frameworks.